Method of Muhammad Mahdi al-Asafi in his interpretation: (in the rehab of the Koran) - Nizamuddin Najm al-Din, Noor (Al-Adab Journal, 2019)
Praise be to Allah, Lord of the Worlds, and prayers and peace be upon the best messengers and on his family and companions, and after ...The diversity of Quranic verses and the different levels of understanding and understanding of its meanings and purposes and the different tastes and tastes of interpreters and the impact of subjective and subjective conditions that cast a shadow over the phenomenon of the interpretation of the interpretation of the emergence of different curricula and schools in the questioning of the divine book and diving deep.What we are interested in here is shedding light on our present book (in the rehab of the Qur'an) and its distinctive approach to the author and his style and the extent of his success in achieving what they are attracted to.The interpretative effort of the Sheikh Al-Asafi can not be limited to what is included in the contents of this book only. The Sheikh's questioning of the Holy Qur'an and its use of it almost invariably overtakes his intellectual achievements. The influence of the Qur'an on his scientific career is not hidden even to the general public